(untitled) (Journal of Parents and Teachers, 2012)
The development of a God experience implies that the kid opens him/herself to “love the Lord with all his/her heart and with all his/her soul and with all his/her mind and love his/her neighbor as him/herself”, it means, he develops an experience of a relationship with God. The evolutionary psychology invites us to think in an opposite way. The kid must learn to be loved, to love him/herself, to love his/her neighbor and from these experiences the kid starts a relationship with God. In this article we will see this process in light of evolutionary psychology, especially during the first years.